Phenolics extraction from sweet potato peels: key factors screening through a placket-burman design - Anastácio, Ana (2012)
Sweet potato peels usually considered as waste in food service operations may be upgraded into value added functional foods with high phenolic content and antioxidant activity. The effect of nine extraction variables was identified as relevant in previous phenolics extraction studies, because solvent solid ratio, time, pH, peeling cut depth, particle size, temperature, solvent, sample amount and agitation were combined in a 12 run Placket–Burman design to screen for key factors. The extraction of phenolic compounds was only significantly (p < 0.05) affected by solvent:solid ratio (positively) and peel cut depth (negatively) with similar effect magnitude. These factors effects presented similar direction, size and significance on extracts antioxidant activity measured by FRAP. Regression models on FRAP transformed by squared root function revealed the two factor interaction peel cut depth and sample amount as the third most influencing factor. Beyond the usage of sweet potato peels as a new constituent for human food, it should also be tested for ingredient optimized in the production of functional foods.